Analysis of muscle activity in various performance levels of Ollie jumps in skateboarding: A pilot study - Michal Vorlíček; Zdeněk Svoboda; Markéta Procházková (Palacký University Olomouc, 2015)
Background: Correct mastering of a basic Ollie jump is essential for development of other jumps in skateboarding. In scientific literature we can find a lack of scientifically proved knowledge that describes the difference in muscular activity on various levels of this jump performance. Objective: The aim of this study was to characterize muscular activity in the basic skateboard Ollie jump and to compare this activity with a more difficult modification of the switchstance Ollie jump (the same jump but changed position of limbs). Methods: Ten men experienced in skateboarding for several years, aged 20.0 ± 4.6 years participated in the study (height 1.79 ± 0.05 m, body mass 71.5 ± 4.1 kg). All subjects performed 3 measured Ollie jumps and after that 3 switchstance Ollie jumps. In case of the last-mentioned front and back lower limbs are switched. The observation of muscular activity was carried out by the Delsys Trigno electromyography system. The jump was divided (after video records) into four phases: preparatory, take-off, flight-up and landing. Mean amplitude of muscle activity was measured in following muscles: tibialis anterior, gastrocnemius medialis, rectus femoris, semitendinosus and gluteus medius. Comparison of muscle activity during Ollie and switchstance Ollie was performed by the Wilcoxon test in Statistica. Results: Significantly greater activity (p < .05) was shown by gastrocnemius medialis and rectus femoris on the lower back limb during the preparatory phase of switchstance Ollie and by tibialis anterior and semitendinosus on lower front limb during the landing phase of Ollie. Conclusion: Results of our study suggest that in switchstance Ollie is increased muscle activity during preparation period on the back limb and movement control during landing. The skaters in this type of jump should move his/her centre of gravity from the tail to the centre of the skateboard and also he/she would produce adequate muscle activity also during the landing phase.